Effect of Artificial Humic Acids Derived from Municipal Sludge on Plant Growth, Soil Fertility, and Dissolved Organic Matter - Rongting Ji; Chenwei Liu; Qiujin Xu; Yue Zhang; Mei Chen; Longjiang Zhang; Feilong Hu (Agriculture)
Due to its high nutrient utilization efficiency, liquid organic fertilizer has become a research hotspot in the field of agricultural planting. Artificial humic acids, which are near-nature products, can be deemed as a green liquid organic fertilizer, but few studies have been reported, which has limited their further application. In this study, artificial humic acids were derived from municipal sludge, and their effect on rice growth, soil fertility, and dissolved organic matter was investigated using multi-chamber root box experiments. The shoot and root biomass of rice can be significantly enhanced by artificial humic acids, and the heavy metal concentration in rice was within safe limits. Artificial humic acids can limit the decrease in soil pH, especially in the far-rhizosphere zone, and improve the distribution of nutrients in the rhizosphere, near-rhizosphere, and far-rhizosphere zones. The use of artificial humic acids led to a significant decrease in soil electrical conductivity. The dissolved organic carbon content in the root zone was significantly increased, and the fluorescence intensity of dissolved organic matter in the rhizosphere was significantly increased. The proportion of specific components of dissolved organic matter was just slightly changed in the rhizosphere and near-rhizosphere zones. Artificial humic acids promoted the humification of dissolved organic matter in the near-rhizosphere and far-rhizosphere zones. The findings indicate that the environmental impact of artificial humic acids is significantly different from conventional chemical fertilizers, and they show huge potential in the agriculture field.